2010
DOI: 10.1038/cmi.2010.45
|View full text |Cite
|
Sign up to set email alerts
|

2-Gy whole-body irradiation significantly alters the balance of CD4+CD25−T effector cells and CD4+CD25+Foxp3+T regulatory cells in mice

Abstract: CD4 1 CD25 1 T regulatory (Treg) cells are critical in inducing and maintaining immunological self-tolerance as well as transplant tolerance. The effect of low doses of whole-body irradiation (WBI) on CD4 1 CD25 1 Foxp3 1 Treg cells has not been determined. The proportion, phenotypes and function of CD4 1 CD25 1 Treg cells were investigated 0.5, 5 and 15 days after euthymic, thymectomized or allogeneic bone marrow transplanted C57BL/6 mice received 2-Gy c-rays of WBI. The 2-Gy WBI significantly enhanced the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 52 publications
6
46
0
Order By: Relevance
“…Although there were main eff ects of radiation in all three of the cytokines we assessed, these eff ects only occurred in the E. coli -treated mice and will be discussed below. A lack of a signifi cant response in these cytokines after radiation alone is consistent with a previous report by Qu et al (2010) using reverse transcription polymerase chain reaction (RT-PCR) to assess several cytokines. In that study, there were minimal changes in splenic IL-6 and TNF-α 1 -3 days after 2 Gy gamma-irradiation.…”
Section: Oxidative Burstsupporting
confidence: 87%
See 2 more Smart Citations
“…Although there were main eff ects of radiation in all three of the cytokines we assessed, these eff ects only occurred in the E. coli -treated mice and will be discussed below. A lack of a signifi cant response in these cytokines after radiation alone is consistent with a previous report by Qu et al (2010) using reverse transcription polymerase chain reaction (RT-PCR) to assess several cytokines. In that study, there were minimal changes in splenic IL-6 and TNF-α 1 -3 days after 2 Gy gamma-irradiation.…”
Section: Oxidative Burstsupporting
confidence: 87%
“…So their increase in response to E. coli is not surprising. However, these cytokine are primarily released by activated macrophages, T cells and B cells, all shown to be reduced by radiation here and elsewhere , 2003a, Pecaut and Gridley 2008, Qu et al 2010. Furthermore, radiation did not appear to have any eff ect on these cytokines in the absence of an immune challenge.…”
Section: Oxidative Burstmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition to killing radiosensitive immune cells, ionizing radiation can induce microenvironmental changes in the tumor milieu and thereby regulate the Th1/Th2 balance (3). It has been observed that whole-body irradiation with c rays decreases the lymphocyte pool significantly, and that various lymphocyte populations have variable sensitivities to c radiation (4,5). Early reports showing that radiation exposure could slow the growth of transplanted tumors through the enhancement of the anticancer immune response in total-body irradiation mouse model (6), drew attention toward the use of radiation as an immunological adjuvant to enhance tumor control.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a similar breakdown of checkpoint regulation, plausibly due to an IL-2/αIL-2-mediated effect on insulinreactive T cells, which are prominent in 6-week old NOD mice, or other potentially diabetogenic immune cells. Some evidence suggests lymphopenia, observed in the present study, is detrimental for tolerance induction due to the reduced recovery of Treg (Kaminitz et al, 2010), although, other studies have suggested Treg are less susceptible to irradiation-induced apoptosis (Qu et al, 2010a;Qu et al, 2010b). The effect of irradiation-induced lymphopenia may contribute to the different effects of proinsulin-encoding BM/HSPC transfer on diabetes development at different disease stages.…”
Section: Discussionmentioning
confidence: 38%